2020
DOI: 10.4314/ejhs.v30i6.5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Antibiotic Resistant diarrheagenic Escherichia coli pathotypes isolated from Children with Diarrhea in Nairobi City, Kenya

Abstract: BACKGROUND፡ The marked genome plasticity of diarrheagenic Escherichia coli promotes emergence of pathotypes displaying unique phenotypic and genotypic resistance. This study examined phenotypic and genotypic antibiotic resistant diarrheagenic Escherichia coli pathotypes among children in Nairobi City, Kenya.METHODS: In a cross-sectional study, diarrheagenic Escherichia coli pathotypes were isolated from stool samples and their phenotypic and genotypic resistance against eight antimicrobial agents assayed.RESUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
3
11
1
Order By: Relevance
“…Our findings show that the most prevalent pathogens were EPEC, EAEC, and ETEC. Similar to previous reports from other African countries, including Kenya [18], Mozambique [29], Sudan [7], and Rwanda [26], about half the samples tested were positive for at least one DEC pathotype. Although these pathogens are not routinely screened for in Zambia due to the requirement of molecular tools for definitive diagnosis, recent research including our work affirms that DECs significantly contribute to diarrhoea among children.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings show that the most prevalent pathogens were EPEC, EAEC, and ETEC. Similar to previous reports from other African countries, including Kenya [18], Mozambique [29], Sudan [7], and Rwanda [26], about half the samples tested were positive for at least one DEC pathotype. Although these pathogens are not routinely screened for in Zambia due to the requirement of molecular tools for definitive diagnosis, recent research including our work affirms that DECs significantly contribute to diarrhoea among children.…”
Section: Discussionsupporting
confidence: 88%
“…Most of the infants in our study were reported to be breastfeeding; however, we observed an overall high prevalence of DEC among them. Although breast milk is known to have a protective effect against infectious diarrhoea among children, other factors such as suboptimal breastfeeding and poor hygienic practices among caregivers may contribute to diarrhoea among infants [17,18]. Although not significantly associated with DEC positivity, we noted that more than half of the children presenting with diarrhoea did not have water piped into the yard but rather used public taps or wells.…”
Section: Discussionmentioning
confidence: 52%
“…In the present study, DEC of children with diarrhea showed higher resistance to trimethoprim/sulfamethoxazole (82.1%), amoxicillin (79.5%), ampicillin (74.4%), and gentamicin (69.2%). This finding agrees with the resistance reported recently in Kenya [ 48 ]. In Burkina Faso, Bonko et al [ 92 ] also reported that isolates from children under five exhibited a high resistance rate to trimethoprim-sulphamethoxazole (100%), ampicillin (100%), ciprofloxacin (71.4%).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings revealed that 39 (49.4%) DEC possess various virulence genes, including st , lt, aatA , eae , stx2 , and hlyA that enable them to cause diarrheagenic illness. The proportion of DEC detected in this study was higher than the 20.6% to 36.4% reported from Iran [ 47 ], Kenya [ 48 ], and Egypt [ 49 ]. A similar finding with a higher frequency of pathogenic E. coli was documented in Nigeria [ 46 ], Gabon [ 50 ], Iraq [ 51 ], Guinea Bissau [ 52 ], and Sudan [ 53 ].…”
Section: Discussioncontrasting
confidence: 87%
“…Outside Iraq, a study in Iran by Mahdavi Broujerdi et al [21] referred to that the EAEC was more detected and EPEC EIEC and ETEC were identified in low percentages while EHEC was not detected. A study in Kenya showed the EAEC was widely identified followed by EIEC, ETEC, and EPEC [22]. The differences in the prevalence of DEC pathotypes are due to the differences in geographic regions, development of countries, isolation season, and ages involved in studies [16].…”
Section: Discussionmentioning
confidence: 99%